Producers' make or buy decision and business shutdown: An evaluation of choice in textile industry - Kenneth Enoch Okpala; Sunday Mlanga; Anulika Odochi Nwajiuba; Chimsunum Osanebi; Chuks Marcel Ezemoyih (Cogent Business & Management, 2019)
The problem of textile industry started with the economic recession of the 1980s and was aggravated by globalization coupled with poor infrastructure and Nigerians perception of made in Nigeria goods. This helped the foreign multi-national textile manufacturing giants to dominate Nigeria textile market leading to the collapse of many viable local textile mills with chains of effects such as expanded unemployment level, increased poverty rates with its associated social vices, reduction in government tax revenue and loss of investors' funds in Nigeria. This study evaluated the producers' make or buy decision and organizational shutdown in the textile industry as a means of resolving the issues. Descriptive survey research design used and the population consisted of 12 active textile companies with 714 management staff. 6 textile mills with 403 staff representing 50% of the population were used as sample size. The validity and reliability of the instrument were established. Primary data collected were analyzed using descriptive and regression analysis method at 5% level of significance. The result obtained concluded that the sub-variables of the independent-cost, capacity and quality control have significant impacts on Nigerian textile mills closure (R = .776, R2 = .721, p < .05; R = .702, R2 = .683, p < .05; R = .658, R2 = .635, p < .05). The study recommended that instead of the complete shutdown of the textile mills, management of such organizations should have resort to buying from outside suppliers to meet customers demand and survive, maintain their staff, save investors' fund and contribute their quota to the economy.
Keywords: 650; management accounting; make or buy decision; multi-fiber arrangement; company; shutdown; textile industry